Two ATAF transcription factors ANAC102 and ATAF1 contribute to the suppression of cytochrome P450‐mediated brassinosteroid catabolism in Arabidopsis. Issue 3 (7th February 2021) - Peng, Hao; Neff, Michael M.
Abstract: PHYB ACTIVATION TAGGED SUPPRESSOR 1 (BAS1) and SUPPRESSOR OF PHYB‐4 7 (SOB7) are two cytochrome P450 enzymes that inactivate brassinosteroids (BRs) in Arabidopsis . The NAC transcription factor (TF) ATAF2 (ANAC081) and the core circadian clock regulator CIRCADIAN CLOCK ASSOCIATED 1 (CCA1) both suppress the expression of BAS1 and SOB7 via direct promoter binding. Additionally, BRs cause feedback suppression on ATAF2 expression. Here, we report that two ATAF‐subgroup TFs, ANAC102 and ATAF1 (ANAC002), also contribute to the transcriptional suppression of BAS1 and SOB7 . ANAC102 and ATAF1 gene‐knockout mutants exhibit elevated expression of both BAS1 and SOB7, expanded tissue‐level accumulation of their protein products and reduced hypocotyl growth in response to exogenous BR treatments. Similar to ATAF2, both ANAC102 and ATAF1 are transcriptionally suppressed by BRs and white light. Neither BAS1 nor SOB7 expression is further elevated in ATAF double or triple mutants, suggesting that the suppression effect of these three ATAFs is not additive. In addition, ATAF single, double, and triple mutants have similar levels of BR responsiveness with regard to hypocotyl elongation. ATAF2, ANAC102, ATAF1, and CCA1 physically interact with itself and each other, suggesting that they may coordinately suppress BAS1 and SOB7 expression via protein–protein interactions. Despite the absence of CCA1‐binding elements in their promoters, ANAC102 and ATAF1 have similar transcript circadian oscillation patterns as that of CCA1, suggesting that these two ATAF genes may be indirectly regulated by the circadian clock.